Raw material composition of positive electrode material, positive electrode material, preparation method thereof, electrode sheet and battery

CN122992058APending Publication Date: 2026-10-27SHANGHAI SUNRISE POLYMER MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610786446.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-02
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本发明要解决的技术问题是为了克服现有技术中的碳源存在一些不足导致所得正极材料制得的电池电化学性能较差的缺陷,提供一种正极材料的原料组合物、正极材料及其制备方法、极片和电池

Benefits of technology

采用本申请的正极材料的原料组合物制得的正极材料具有较低的粉末电阻率和较佳的压实密度;由该正极材料制得的电池具有较佳的电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_23
    Figure SMS_23
  • Figure SMS_24
    Figure SMS_24
  • Figure SMS_25
    Figure SMS_25
Patent Text Reader

Abstract

The application discloses a raw material composition of a positive electrode material, a positive electrode material, a preparation method of the positive electrode material, a pole piece and a battery. The raw material composition of the positive electrode material comprises a carbon source; and the carbon source comprises an amine ether compound. The positive electrode material prepared by using the raw material composition of the positive electrode material has low powder resistivity and better compaction density; and the battery prepared from the positive electrode material has better electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a raw material composition for a positive electrode material, a positive electrode material and its preparation method, an electrode sheet, and a battery. Background Technology

[0002] Lithium-ion battery cathode materials (such as lithium iron phosphate, ternary materials, and lithium-rich manganese-based materials) generally suffer from low electronic conductivity and limited ion diffusion rates, directly resulting in battery rate performance, cycle stability, and low-temperature discharge performance failing to meet the demands of high-end applications. Currently, carbon coating modification is the mainstream technology used in the industry to improve the conductivity of cathode materials. By constructing a continuous and uniform carbon conductive network on the surface of cathode material particles, interfacial impedance is reduced, promoting rapid electron transport.

[0003] In existing technologies, the carbon sources used for carbon coating of cathode materials are mostly traditional carbon sources such as glucose, sucrose, starch, citric acid, phenolic resin, and asphalt. These carbon sources have many inherent defects in practical applications: On the one hand, small-molecule sugar carbon sources are prone to rapid decomposition, volatilization, and migration during high-temperature sintering, making it difficult to form a continuous and dense carbon layer on the particle surface. This can easily lead to uneven carbon layer thickness, local exposure, or even detachment, resulting in poor integrity of the conductive network. On the other hand, some organic polymer carbon sources have a low pyrolysis recarbon ratio, which can easily generate a large amount of gas at high temperatures, causing particle agglomeration and making the coating layer loose and porous with insufficient structural stability. Furthermore, the amorphous carbon formed after pyrolysis of traditional carbon sources has a low degree of graphitization, resulting in limited conductivity improvement. In addition, some carbon sources have poor compatibility with cathode material precursors and uneven dispersion, which can easily lead to local carbon enrichment or insufficient coating. Ultimately, this results in problems such as rapid capacity decay, poor rate performance, and poor high-temperature cycling stability during long-term cycling. It is difficult to balance high conductivity and structural stability, which restricts the further development of high-performance lithium-ion battery cathode materials.

[0004] Therefore, there is an urgent need for a new type of carbon source for preparing cathode materials, which can form a stable and uniform carbon coating layer during high-temperature calcination to further improve the electrochemical performance of the battery obtained from the cathode material. Summary of the Invention

[0005] The technical problem this invention aims to solve is to overcome the shortcomings of existing technologies where insufficient carbon sources lead to poor electrochemical performance in batteries made from the resulting cathode materials. This invention provides a raw material composition for a cathode material, the cathode material itself, a method for preparing the same, an electrode sheet, and a battery. The cathode material prepared using the raw material composition of this application exhibits lower powder resistivity and better compaction density; the battery made from this cathode material demonstrates superior electrochemical performance.

[0006] The present invention solves the above-mentioned technical problems through the following technical solution: The present invention provides a raw material composition for a cathode material, comprising a carbon source; the carbon source comprises an amine ether compound; the amine ether compound accounts for 40%-62% of the mass percentage of the carbon source.

[0007] In this invention, the amine ether compounds refer to a class of compounds obtained by ring-opening polymerization of ethylene oxide and / or propylene oxide with amino-containing amines as initiators.

[0008] In this invention, the amine ether compounds preferably have the structures shown in Formula I and / or Formula II: Formula I; Among them, R1 and R2 are each independently selected from -H, straight chain or branched C. 1-10 Alkyl groups, such as -H.

[0009] Among them, R3 is selected from the C of straight chain or branched chain. 1-20 Alkyl, -M7R9, or phenyl. The straight-chain or branched C... 1-20 Alkyl groups are preferably straight-chain C4 groups. 12 Alkyl groups. In the -M7R9, M7 is selected from... n is selected from 1 to 5000, preferably 5 to 10, for example 6; R 11 Selected from -H, -CH3, or -CH2CH3, for example -H; R9 is selected from -H, straight-chain or branched C. 1-10 Alkyl groups, such as -H; M1 or M2 are each independently selected from n is selected from 1 to 5000, preferably 3 to 10, for example 5; R 11 Selected from -H, -CH3, or -CH2CH3, for example -H.

[0010] Formula II; Among them, R4 is selected from C of straight chain or branched chain. 2-12 Alkylene or -CH2CH2N(M8R) 10 CH2CH2-. The straight-chain or branched C 2-12 The alkylene group is preferably a straight-chain C2-alkylene group. M8 is selected from... n is selected from 1 to 5000, preferably 3 to 15, for example 7; R 11 Selected from -H, -CH3, or -CH2CH3R5, for example -H; R 10 C selected from -H, straight chain or branched chain 1-10 Alkyl groups, such as -H.

[0011] Among them, R5, R6, R7, and R8 are each independently selected from -H, straight chain, or branched C. 1-10 Alkyl groups, such as -H.

[0012] Among them, M3, M4, M5, or M6 are each independently selected. n is selected from 1-5000, preferably 3-15, for example 6 or 7; R 11 Selected from -H, -CH3, or -CH2CH3, for example -H.

[0013] In a preferred embodiment 1, the amine ether compound has the structure shown in Formula I above, and R3 is selected from C 12 Alkyl; M1 is selected from n is 5, R 11 Selected from -H; R1 is selected from -H; M2 is selected from R 11 Selected from -H, n is 5; R2 is selected from -H.

[0014] In a preferred embodiment 2, the amine ether compound has the structure shown in Formula I above, where R1 is selected from -H; M1 is selected from... R 11 Selected from -H, n is 5; M2 is selected from R 11 Selected from -H, n is 5; R2 is selected from -H; R3 is selected from -M7R9, M7 is selected from R 11 Selected from -H, n is 5, R9 is selected from -H.

[0015] In a preferred embodiment 3, the amine ether compound has the structure shown in Formula I above, where R1 is selected from -H; M1 is selected from... R 11 Selected from -H, n is 5; M2 is selected from R 11 R1 is selected from -H, n is 5; R2 is selected from -H; R3 is selected from phenyl.

[0016] In a preferred embodiment 4, the amine ether compound has the structure shown in Formula II above, where R4 is selected from a straight-chain C2 alkylene group; M3 is selected from... R 11 Selected from -H, n is 6; R5 is selected from -H; M4 is selected from R 11 Selected from -H, n is 6; R6 is selected from -H; M5 is selected from R 11 Selected from -H, n is 6; R7 is selected from -H; M6 is selected from R 11 Selected from -H, n is 6; R8 is selected from -H.

[0017] In a preferred embodiment 5, the amine ether compound has the structure shown in Formula II above, and R4 is selected from -CH2CH2N(M8R 10CH2CH2-; M8 is selected from R 11 Selected from -H, n is 7; R 10 Selected from -H; M3 selected from R 11 Selected from -H, n is 7; R5 is selected from -H; M4 is selected from R 11 Selected from -H, n is 7; R6 is selected from -H; M5 is selected from R 11 Selected from -H, n is 7; R7 is selected from -H; M6 is selected from R 11 Selected from -H, n is 7; R8 is selected from -H.

[0018] In this invention, the amine ether compound accounts for 45%-62% of the mass percentage of the carbon source, for example, 50%, 53.8%, 45.5%, 55.6% or 60%.

[0019] In this invention, the carbon source accounts for 3%-20% of the mass percentage of the raw material composition of the cathode material, preferably 5%-15%, for example 8.9%, 9.5%, 8.2%, 5.3%, 5.8% or 12%.

[0020] In this invention, the carbon source may also include other carbon sources, preferably one or more selected from sucrose, glucose, polyethylene glycol, starch, citric acid, and asphalt, such as polyethylene glycol and / or glucose. The polyethylene glycol is preferably PEG1500, PEG6000, or PEG-200.

[0021] In a preferred embodiment, the carbon source includes glucose and the amine ether compound, and the mass ratio of glucose to the amine ether compound can be (0.3-3):1, preferably (0.5-2):1, for example 1:1, 0.85:1, 1.2:1, 0.8:1 or 0.67:11.

[0022] In a preferred embodiment, the carbon source includes polyethylene glycol and the amine ether compound, and the mass ratio of the polyethylene glycol to the amine ether compound can be (0.5-2):1, preferably (0.8-1.5):1, for example 1:1, 0.8:1 or 1.25:1.

[0023] In a more preferred embodiment, the carbon source comprises dodecylamine polyoxyethylene (10) ether and glucose.

[0024] In a more preferred embodiment, the carbon source comprises triethanolamine polyoxyethylene (15) ether and glucose.

[0025] In a more preferred embodiment, the carbon source includes aniline polyoxyethylene (10) ether and glucose.

[0026] In a more preferred embodiment, the carbon source includes ethylenediamine polyoxyethylene (24) ether and glucose.

[0027] In a more preferred embodiment, the carbon source includes diethylenetriamine polyoxyethylene (35) ether and glucose.

[0028] In a more preferred embodiment, the carbon source comprises dodecylamine polyoxyethylene (10) ether and PEG200.

[0029] In this invention, the raw material composition in the cathode material also includes raw materials conventional in the art.

[0030] In this invention, the cathode material is preferably lithium iron phosphate, lithium manganese iron phosphate, or sodium iron manganese phosphate.

[0031] In a preferred embodiment, the cathode material is lithium iron phosphate, and the raw material composition of the cathode material includes an iron source, a lithium source, a phosphorus source, a carbon source, and a solvent.

[0032] The iron source can be of a type conventional in the art, such as iron phosphate. The lithium source can be of a type conventional in the art, such as lithium carbonate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The phosphorus source is generally added in the form of an aqueous phosphoric acid solution. The mass concentration of phosphoric acid in the aqueous phosphoric acid solution is preferably 75-90 wt%, for example, 85 wt%. The carbon source includes glucose and amine ether compounds; or polyethylene glycol and amine ether compounds. The mass ratio of glucose to the polymer is preferably (0.3-3):1, preferably (0.5-2):1, for example 1:1, 0.85:1, 1.2:1, 0.8:1 or 0.67:11. The mass ratio of polyethylene glycol to the amine ether compound can be (0.5-2):1, preferably (0.8-1.5):1, for example 1:1, 0.8:1 or 1.25:1. The solvent can be of a type conventional in the art, such as water. The preferred mass ratio of the iron source, lithium source, phosphorus source and carbon source is (800-1200):(200-300):(3-9):(80-160), more preferably (900-1100):(210-240):(5-8):(100-140), for example 995:226:6.73:120, 995:226:6.73:130 or 995:226:6.73:110.

[0033] The raw material composition of the cathode material further includes a metal dopant. The metal dopant is preferably one or more of a Ti compound, a V compound, and a Nb compound, more preferably a Ti compound, such as titanium dioxide. The mass ratio of the metal dopant to the iron source is preferably (800-1200):(3-9), more preferably (900-1100):(5-7), for example 995:5.97.

[0034] In a preferred embodiment, the cathode material is lithium manganese iron phosphate, and the raw material composition of the cathode material includes a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source, and a solvent.

[0035] The lithium source can be of a type conventional in the art, such as lithium carbonate. The manganese source can be of a type conventional in the art, such as manganese acetate. The iron source can be of a type conventional in the art, such as ferrous oxalate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The carbon source includes glucose and amine ether compounds; or polyethylene glycol and amine ether compounds. The mass ratio of glucose to the polymer is preferably (0.3-3):1, more preferably (0.5-2):1, for example 1:1, 0.85:1, 1.2:1, 0.8:1 or 0.67:11. The mass ratio of polyethylene glycol to the amine ether compound can be (0.5-2):1, preferably (0.8-1.5):1, for example 1:1, 0.8:1 or 1.25:1. The solvent can be of a type conventional in the art, such as anhydrous ethanol. The preferred mass ratio of the lithium source, manganese source, iron source, phosphorus source, carbon source and solvent is (200-500):(1000-1500):(5-15):(8-20):(50-150):(500-1500), more preferably (300-400):(150-300):(7-11):(10-15):(70-110):(800-1200), for example 350:1250:9:12:90:1000 or 350:1250:9:12:100:1000.

[0036] In a preferred embodiment, the positive electrode material is sodium iron manganese phosphate, and the raw material composition of the positive electrode material includes a sodium source, a phosphorus source, an iron source, a manganese source, a carbon source, and a solvent.

[0037] The sodium source can be conventional in the art, such as sodium carbonate. The phosphorus source can be conventional in the art, such as ammonium dihydrogen phosphate. The iron source can be conventional in the art, such as ferric oxide. The manganese source can be conventional in the art, such as manganese dioxide. The carbon source includes glucose and amine ether compounds; or polyethylene glycol and amine ether compounds. The mass ratio of glucose to the polymer is preferably (0.3-3):1, preferably (0.5-2):1, for example 1:1, 0.85:1, 1.2:1, 0.8:1 or 0.67:11. The mass ratio of polyethylene glycol to the amine ether compound can be (0.5-2):1, preferably (0.8-1.5):1, for example 1:1, 0.8:1 or 1.25:1. The solvent can be conventional in the art, such as water. Based on sodium, iron, manganese, and phosphorus elements, the molar ratio of the sodium source, phosphorus source, iron source, and manganese source is preferably (1-9):(1-5):(0.01-0.1):(1-9), more preferably (3-5):(2-4):(0.01-0.03):(3-5), for example 4:2.98:0.01:4. Based on carbon, iron, and manganese elements, the molar ratio of the carbon source to the iron and manganese sources is preferably (0.2-1):(0.5-3), more preferably (0.3-1):(0.8-1.5), for example 0.5:1.

[0038] The present invention provides a method for preparing a cathode material, comprising the following steps: sintering a precursor slurry to obtain the cathode material; wherein the precursor slurry comprises the raw material composition of the cathode material as described above.

[0039] In this invention, the sintering temperature can be 300-850℃, preferably 400-750℃, for example 480, 550, 700 or 720℃. The sintering time can be 1-20h, preferably 2-13h, for example 2, 7, 8, 10 or 12h.

[0040] In this invention, the sintering is preferably carried out under an inert atmosphere, such as a nitrogen atmosphere.

[0041] In this invention, the heating rate from room temperature to the sintering temperature is preferably 1-10°C / min, more preferably 2-6°C / min, for example 3 or 5°C / min.

[0042] In this invention, the sintering is preferably divided into a single-stage sintering and a two-stage sintering, wherein the temperature of the two-stage sintering is higher than that of the single-stage sintering.

[0043] The sintering temperature of the first stage is preferably 300-600℃, more preferably 400-500℃, for example 480℃. The sintering time of the first stage is preferably 1-4h, more preferably 2-3h, for example 2h. The heating rate from room temperature to the sintering temperature of the first stage is preferably 3-8℃ / min, more preferably 4-6℃ / min, for example 5℃ / min.

[0044] The preferred temperature for the second-stage sintering is 500-850℃, more preferably 650-750℃, for example 700℃. The preferred sintering time for the second stage is 5-10 hours, more preferably 7-9 hours, for example 8 hours. The heating rate from the temperature of the first-stage sintering to the temperature of the second-stage sintering is preferably 1-5℃ / min, more preferably 2-4℃ / min, for example 3℃ / min.

[0045] In a preferred embodiment, the cathode material is lithium iron phosphate, and the preparation method of the cathode material includes the following steps: spray granulation and sintering of the precursor slurry; the precursor slurry includes an iron source, a lithium source, a phosphorus source, a carbon source, and a solvent.

[0046] The iron source can be of a type conventional in the art, such as iron phosphate. The lithium source can be of a type conventional in the art, such as lithium carbonate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The phosphorus source is generally added in the form of an aqueous phosphoric acid solution. The mass concentration of phosphoric acid in the aqueous phosphoric acid solution is preferably 75-90 wt%, for example, 85 wt%. The carbon source includes glucose and amine ether compounds; or polyethylene glycol and amine ether compounds. The mass ratio of glucose to the polymer is preferably (0.3-3):1, preferably (0.5-2):1, for example 1:1, 0.85:1, 1.2:1, 0.8:1 or 0.67:11. The mass ratio of polyethylene glycol to the amine ether compound can be (0.5-2):1, preferably (0.8-1.5):1, for example 1:1, 0.8:1 or 1.25:1. The solvent can be of a type conventional in the art, such as water. The preferred mass ratio of the iron source, lithium source, phosphorus source and carbon source is (800-1200):(200-300):(3-9):(80-160), more preferably (900-1100):(210-240):(5-8):(100-140), for example 995:226:6.73:120, 995:226:6.73:130 or 995:226:6.73:110.

[0047] The solid content of the precursor slurry is preferably 30-60%, more preferably 35-50%, for example 40%. The D50 of the precursor slurry is preferably 250-500nm, more preferably 350-400nm, for example 370-380nm.

[0048] The precursor slurry is preferably obtained by mixing an iron source, a lithium source, a phosphorus source, a carbon source, and a solvent, followed by sand milling. The sand milling time is preferably 60-180 min, more preferably 90-150 min, for example 120 min.

[0049] The precursor slurry preferably also includes a metal dopant. The metal dopant is preferably one or more of a Ti compound, a V compound, and a Nb compound, more preferably a Ti compound, such as titanium dioxide. The mass ratio of the metal dopant to the iron source is preferably (800-1200):(3-9), more preferably (900-1100):(5-7), for example 995:5.97.

[0050] The spray granulation temperature is preferably 180-300℃, more preferably 200-240℃, for example 220℃. During spray granulation, the flow rate of the precursor slurry is preferably 600-1000 ml / h, more preferably 700-900 ml / h, for example 800 ml / h.

[0051] In a preferred embodiment, the cathode material is lithium manganese iron phosphate, and the preparation method of the cathode material includes the following steps: sintering a precursor slurry; the precursor slurry includes a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source, and a solvent.

[0052] The lithium source can be of a type conventional in the art, such as lithium carbonate. The manganese source can be of a type conventional in the art, such as manganese acetate. The iron source can be of a type conventional in the art, such as ferrous oxalate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The carbon source includes glucose and amine ether compounds; or polyethylene glycol and amine ether compounds. The mass ratio of glucose to the polymer is preferably (0.3-3):1, more preferably (0.5-2):1, for example 1:1, 0.85:1, 1.2:1, 0.8:1 or 0.67:11. The mass ratio of polyethylene glycol to the amine ether compound can be (0.5-2):1, preferably (0.8-1.5):1, for example 1:1, 0.8:1 or 1.25:1. The solvent can be of a type conventional in the art, such as anhydrous ethanol. The preferred mass ratio of the lithium source, manganese source, iron source, phosphorus source, carbon source and solvent is (200-500):(1000-1500):(5-15):(8-20):(50-150):(500-1500), more preferably (300-400):(150-300):(7-11):(10-15):(70-110):(800-1200), for example 350:1250:9:12:90:1000 or 350:1250:9:12:100:1000.

[0053] The precursor slurry is preferably obtained by ball milling a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source, and a solvent. The ball milling speed is preferably 200-400 r / min, more preferably 250-300 r / min, for example, 280 r / min. The ball milling time is preferably 1-7 h, more preferably 3-5 h, for example, 4 h. The ball-to-material ratio during ball milling is preferably (4-12):1, more preferably (6-10):1, for example, 8:1.

[0054] Prior to sintering, the precursor slurry preferably undergoes a process of solvent removal and particle size control. The solvent removal method can be conventional in the art, such as vacuum drying. The vacuum drying temperature is preferably 40-70°C, more preferably 50-60°C, for example 55°C. The vacuum drying time is preferably 5-12 hours, more preferably 6-10 hours, for example 8 hours. The particle size control method can be conventional in the art, such as grinding. The endpoint of particle size control is preferably that the material can pass through a 100-mesh sieve.

[0055] The sintering is preferably divided into a single-stage sintering and a two-stage sintering, wherein the temperature of the two-stage sintering is higher than that of the single-stage sintering.

[0056] The sintering temperature of the first stage is preferably 300-600℃, more preferably 400-500℃, for example 480℃. The sintering time of the first stage is preferably 1-4h, more preferably 2-3h, for example 2h. The heating rate from room temperature to the sintering temperature of the first stage is preferably 3-8℃ / min, more preferably 4-6℃ / min, for example 5℃ / min.

[0057] The preferred temperature for the second-stage sintering is 500-850℃, more preferably 650-750℃, for example 700℃. The preferred sintering time for the second stage is 5-10 hours, more preferably 7-9 hours, for example 8 hours. The heating rate from the temperature of the first-stage sintering to the temperature of the second-stage sintering is preferably 1-5℃ / min, more preferably 2-4℃ / min, for example 3℃ / min.

[0058] In a preferred embodiment, the cathode material is sodium iron manganese phosphate, and the preparation method of the cathode material includes the following steps: calcining a precursor slurry; the precursor slurry includes a sodium source, a phosphorus source, an iron source, a manganese source, a carbon source, and a solvent.

[0059] The sodium source can be conventional in the art, such as sodium carbonate. The phosphorus source can be conventional in the art, such as ammonium dihydrogen phosphate. The iron source can be conventional in the art, such as ferric oxide. The manganese source can be conventional in the art, such as manganese dioxide. The carbon source includes glucose and amine ether compounds; or polyethylene glycol and amine ether compounds. The mass ratio of glucose to the polymer is preferably (0.3-3):1, preferably (0.5-2):1, for example 1:1, 0.85:1, 1.2:1, 0.8:1 or 0.67:11. The mass ratio of polyethylene glycol to the amine ether compound can be (0.5-2):1, preferably (0.8-1.5):1, for example 1:1, 0.8:1 or 1.25:1. The solvent can be conventional in the art, such as water. Based on sodium, iron, manganese, and phosphorus elements, the molar ratio of the sodium source, phosphorus source, iron source, and manganese source is preferably (1-9):(1-5):(0.01-0.1):(1-9), more preferably (3-5):(2-4):(0.01-0.03):(3-5), for example 4:2.98:0.01:4. Based on carbon, iron, and manganese elements, the molar ratio of the carbon source to the iron and manganese sources is preferably (0.2-1):(0.5-3), more preferably (0.3-1):(0.8-1.5), for example 0.5:1.

[0060] The solid content of the precursor slurry is preferably 30-60 wt%, more preferably 45-55 wt%, for example 50 wt%.

[0061] The precursor slurry is preferably obtained by mixing a sodium source, a phosphorus source, an iron source, a manganese source, a carbon source, and a solvent, followed by sand milling. The sand milling speed is preferably 1400-2600 r / min, more preferably 1800-2200 r / min, for example, 2000 r / min. The sand milling time is preferably 3-10 h, more preferably 5-7 h, for example, 6 h.

[0062] The preferred temperature for spray granulation is 180-300℃, more preferably 200-240℃, such as 250℃.

[0063] The sintering temperature can be 300-850℃, preferably 400-750℃, for example 480, 550, 700 or 720℃. The sintering time can be 1-20h, preferably 2-13h, for example 2, 7, 8, 10 or 12h. The heating rate from room temperature to the sintering temperature is preferably 1-10℃ / min, more preferably 2-6℃ / min, for example 3 or 5℃ / min.

[0064] In this invention, amine ether compounds are selected as one of the carbon sources for preparing the cathode material. On the one hand, the nitrogen atoms in the molecular structure of amine ether compounds have lone pairs of electrons, which can attract the charge on the surface of the cathode active material, promoting the adsorption of amine ether compounds on the surface of the cathode active material. This allows the amine ether compounds to be uniformly adsorbed on the surface of the cathode active material, thereby forming a uniform carbon coating layer in the subsequent calcination stage. On the other hand, the nitrogen atoms in the molecular structure of amine ether compounds are conducive to the formation of ring structures during the cracking process of the carbon source, thereby generating ordered coated carbon on the surface of the cathode active material.

[0065] This invention provides a cathode material, which is prepared using the cathode material preparation method described above.

[0066] The present invention provides an electrode sheet comprising the positive electrode material as described above.

[0067] The present invention provides a battery comprising the electrodes as described above.

[0068] The positive and progressive effects of this invention are as follows: The cathode material prepared using the raw material composition of the cathode material of this application has a lower powder resistivity and a better compaction density; the battery made from the cathode material has better electrochemical performance. Detailed Implementation

[0069] The present invention will be further illustrated by way of embodiments below, but the present invention is not limited to the scope of the embodiments described herein.

[0070] The structural formulas of the amine ether compounds used in the following examples or comparative examples are as follows: 1. Dodecylamine polyoxyethylene (10) ether: CH3-(CH2) 11 -N((CH2CH2O)5-H)2 2. Triethanolamine polyoxyethylene (15) ether: N(CH2CH2O(CH2CH2O)5H)3 3. Aniline polyoxyethylene (10) ether: C6H5N((CH2CH2O)5H)2 4. Ethylenediamine polyoxyethylene (24) ether: (HO(CH2CH2O)6)2N-CH2CH2-N(CH2CH2O)6H)2 5. Diethylenetriamine polyoxyethylene (35) ether: N((CH2CH2O)7H)2-CH2CH2-N((CH2CH2O)7H)-CH2CH2-N((CH2CH2O)7H)2

[0071] I. Preparation of Lithium Iron Phosphate Materials

[0072] Example 1

[0073] The raw material composition of the cathode material includes: dodecylamine polyoxyethylene (10) ether and glucose as carbon sources; iron phosphate, lithium carbonate, and phosphoric acid aqueous solution as iron source, lithium source, and phosphorus source, respectively; and titanium dioxide as a metal dopant. The carbon source accounts for 8.9% by mass in the raw material composition of the cathode material, and amine ether compounds account for 50% by mass of the carbon source. 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of 85%wt phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose, and 60 parts of dodecylamine polyoxyethylene (10) ether were added to a sand mill (WSP-0.5 of Changzhou Longxin Intelligent Equipment Co., Ltd.) and water was added. The mixture was sand milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380nm. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate cathode material.

[0074] The obtained lithium iron phosphate cathode material was crushed to a particle size of D50=1.2-1.3μm using a traditional Chinese medicine crusher (Teruisi traditional Chinese medicine pulverizer); the particle size was tested using a Malvern Panaco Mastersizer-3000 laser particle size analyzer.

[0075] Example 2

[0076] The only difference from Example 1 is that: the dodecylamine polyoxyethylene (10) ether is replaced with triethanolamine polyoxyethylene (15) ether, and the amount added is 70 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 9.5%; and the mass percentage of amine ether compounds in the carbon source is 53.8%.

[0077] Example 3

[0078] The only difference from Example 1 is that: dodecylamine polyoxyethylene (10) ether is replaced with aniline polyoxyethylene (10) ether, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of amine ether compounds in the carbon source is 50%.

[0079] Example 4

[0080] The only difference from Example 1 is that: the dodecylamine polyoxyethylene (10) ether is replaced with ethylenediamine polyoxyethylene (24) ether, and the amount added is 50 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.2%; and the mass percentage of amine ether compounds in the carbon source is 45.5%.

[0081] Example 5

[0082] The only difference from Example 1 is that: the dodecylamine polyoxyethylene (10) ether is replaced with diethylenetriamine polyoxyethylene (35) ether, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of amine ether compounds in the carbon source is 50%.

[0083] Example 6

[0084] The only difference from Example 1 is that 60 parts of glucose are replaced with 60 parts of PEG200; the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of amine ether compounds in the carbon source is 50%.

[0085] Comparative Example 1

[0086] The only difference from Example 1 is that: dodecylamine polyoxyethylene (10) ether is replaced with polyethylene glycol PEG1500, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of amine ether compounds in the carbon source is 0%.

[0087] Comparative Example 2

[0088] The only difference from Example 1 is that: dodecylamine polyoxyethylene (10) ether is replaced with polyethylene glycol PEG6000, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of amine ether compounds in the carbon source is 0%.

[0089] Comparative Example 3

[0090] The only difference from Example 1 is that only 60 parts of glucose are added, and no dodecylamine polyoxyethylene (10) ether is added; the mass percentage of carbon source in the raw material composition of the cathode material is 4.6%; and the mass percentage of amine ether compounds in the carbon source is 0%.

[0091] Comparative Example 4

[0092] The only difference from Example 1 is that only 60 parts of dodecylamine polyoxyethylene (10) ether are added, and glucose is not added; the mass percentage of carbon source in the raw material composition of the cathode material is 4.6%; and the mass percentage of amine ether compounds in the carbon source is 100%.

[0093] Comparative Example 5

[0094] The only difference from Example 1 is that the amount of dodecylamine polyoxyethylene (10) ether added is reduced to 20 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 6.1%; and the mass percentage of amine ether compounds in the carbon source is 25%.

[0095] The only difference between Comparative Example 6 and Example 1 is that the amount of dodecylamine polyoxyethylene (10) ether added is increased to 100 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 11.5%; and the mass percentage of amine ether compounds in the carbon source is 62.5%.

[0096] II. Preparation of Lithium Manganese Iron Phosphate Materials

[0097] Example 7

[0098] The raw material composition of the cathode material includes: dodecylamine polyoxyethylene (10) ether and glucose as carbon sources; lithium carbonate, manganese acetate, ferrous oxalate and phosphoric acid as lithium source, manganese source, iron source and phosphorus source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 5.3%; amine ether compounds account for 55.6% of the mass percentage of carbon source; 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 50 parts dodecylamine polyoxyethylene (10) ether, 12 parts phosphoric acid and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 and a rotation speed of 280 r / min to obtain precursor slurry. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate cathode material.

[0099] Example 8

[0100] The only difference from Example 7 is that: the dodecylamine polyoxyethylene (10) ether is replaced with triethanolamine polyoxyethylene (15) ether, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 5.8%; and the mass percentage of amine ether compounds in the carbon source is 60%.

[0101] Example 9

[0102] The only difference from Example 7 is that: dodecylamine polyoxyethylene (10) ether is replaced with aniline polyoxyethylene (10) ether, and the amount added is 50 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 5.3%; and the mass percentage of amine ether compounds in the carbon source is 55.6%.

[0103] Example 10

[0104] The only difference from Example 7 is that: the dodecylamine polyoxyethylene (10) ether is replaced with ethylenediamine polyoxyethylene (24) ether, and the amount added is 50 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 5.3%; and the mass percentage of amine ether compounds in the carbon source is 55.6%.

[0105] Example 11

[0106] The only difference from Example 7 is that: the dodecylamine polyoxyethylene (10) ether is replaced with diethylenetriamine polyoxyethylene (35) ether, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 5.8%; and the mass percentage of amine ether compounds in the carbon source is 60%.

[0107] Example 12

[0108] The only difference from Example 7 is that 40 parts of glucose are replaced with 40 parts of PEG200; the mass percentage of carbon source in the raw material composition of the cathode material is 5.3%; and the mass percentage of amine ether compounds in the carbon source is 55.6%.

[0109] Comparative Example 7

[0110] The only difference from Example 7 is that: the dodecylamine polyoxyethylene (10) ether is replaced with polyethylene glycol PEG1500, and the amount added is 50 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 5.3%; and the mass percentage of amine ether compounds in the carbon source is 0%.

[0111] Comparative Example 8

[0112] The only difference from Example 7 is that: the dodecylamine polyoxyethylene (10) ether is replaced with polyethylene glycol PEG6000, and the amount added is 50 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 5.3%; and the mass percentage of amine ether compounds in the carbon source is 0%.

[0113] Comparative Example 9

[0114] The only difference from Example 7 is that only 40 parts of glucose are added, and no dodecylamine polyoxyethylene (10) ether is added; the mass percentage of carbon source in the raw material composition of the cathode material is 2.3%; and the mass percentage of amine ether compounds in the carbon source is 0%.

[0115] Comparative Example 10

[0116] The only difference from Example 7 is that only 50 parts of dodecylamine polyoxyethylene (10) ether are added as a carbon source, and glucose is not added; the mass percentage of carbon source in the raw material composition of the cathode material is 2.9%; and the mass percentage of amine ether compounds in the carbon source is 100%.

[0117] Comparative Example 11

[0118] The only difference from Example 7 is that the amount of dodecylamine polyoxyethylene (10) ether added is reduced to 20 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 3.5%; and the mass percentage of amine ether compounds in the carbon source is 33.3%.

[0119] Comparative Example 12

[0120] The only difference from Example 7 is that the amount of dodecylamine polyoxyethylene (10) ether added is increased to 80 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 7.0%; and the mass percentage of amine ether compounds in the carbon source is 66.7%.

[0121] III. Preparation of Sodium Iron Manganese Phosphate Cathode Material for Sodium-Ion Batteries

[0122] Example 13

[0123] The raw material composition of the positive electrode material includes: dodecylamine polyoxyethylene (10) ether and glucose as carbon sources; sodium carbonate, ammonium dihydrogen phosphate, ferric oxide and manganese dioxide as sodium source, phosphorus source, iron source and manganese source, respectively; the mass percentage of carbon source in the raw material composition of the positive electrode material is 12%; amine ether compounds account for 50% of the mass percentage of carbon source; Glucose and dodecylamine polyoxyethylene (10) ether were mixed in a mass ratio of 1:1 as a carbon source. The molar ratio of sodium, iron, manganese and phosphorus in the raw materials was controlled to be 4:2.98:0.01:4, and the molar ratio of the carbon source (calculated as carbon) to the sum of the molar amounts of iron and manganese was 0.5:1. The raw material composition of the cathode material and water were put into a sand mill and ground at a speed of 2000 r / min for 6 h to obtain a precursor slurry with a solid content of 50 wt% during grinding. The mixture was prepared into a dry precursor powder at 250 °C using a spray drying method. The precursor powder was placed in a box furnace and calcined at 550 °C for 12 h under a N2 atmosphere and then naturally cooled to obtain sodium iron manganese sodium phosphate cathode material for sodium-ion batteries.

[0124] Example 14

[0125] The only difference from Example 13 is that: dodecylamine polyoxyethylene (10) ether is replaced with triethanolamine polyoxyethylene (15) ether; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of amine ether compounds in the carbon source is 50%.

[0126] Example 15

[0127] The only difference from Example 13 is that: dodecylamine polyoxyethylene (10) ether is replaced with aniline polyoxyethylene (10) ether; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of amine ether compounds in the carbon source is 50%.

[0128] Example 16

[0129] The only difference from Example 13 is that: dodecylamine polyoxyethylene (10) ether is replaced with ethylenediamine polyoxyethylene (24) ether; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of amine ether compounds in the carbon source is 50%.

[0130] Example 17

[0131] The only difference from Example 13 is that: dodecylamine polyoxyethylene (10) ether is replaced with diethylenetriamine polyoxyethylene (35) ether; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of amine ether compounds in the carbon source is 50%.

[0132] Example 18

[0133] The only difference from Example 13 is that glucose is replaced with PEG200 and the mass percentage of amine ether compounds in the carbon source is 50%.

[0134] Comparative Example 13

[0135] The only difference from Example 13 is that: dodecylamine polyoxyethylene (10) ether is replaced with polyethylene glycol PEG1500; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of amine ether compounds in the carbon source is 0%.

[0136] Comparative Example 14

[0137] The only difference from Example 13 is that: dodecylamine polyoxyethylene (10) ether is replaced with polyethylene glycol PEG6000; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of amine ether compounds in the carbon source is 0%.

[0138] Comparative Example 15

[0139] The only difference from Example 13 is that only glucose is added and no dodecylamine polyoxyethylene (10) ether is added; the mass percentage of carbon source in the raw material composition of the cathode material is 6%; and the mass percentage of amine ether compounds in the carbon source is 0%.

[0140] Comparative Example 16

[0141] The only difference from Example 13 is that only dodecylamine polyoxyethylene (10) ether is added, and glucose is not added; the mass percentage of carbon source in the raw material composition of the cathode material is 6%; and the mass percentage of amine ether compounds in the carbon source is 100%.

[0142] Example 1

[0143] 1. The residual carbon content of the lithium iron phosphate cathode materials prepared in the examples and comparative examples after sintering was tested using a Shanghai Dekai HCS-140 high-frequency infrared carbon-sulfur analyzer.

[0144] 2. The powder resistivity and compaction density of the sintered lithium iron phosphate cathode material were tested using the Xiamen Yuaneng four-probe powder resistivity PRCD2110.

[0145] The test results are shown in Table 1.

[0146] 3. The powder conductivity of the sintered lithium manganese iron phosphate cathode material was tested using the Xiamen Yuaneng four-probe powder resistivity PRCD2110.

[0147] The test results are shown in Table 2.

[0148] Example 2

[0149] 1. Batteries prepared using lithium iron phosphate as the positive electrode active material

[0150] The crushed lithium iron phosphate cathode material (LiFePO4) obtained in the above examples and comparative examples was mixed with the above raw materials in a mass ratio of LiFePO4:conductive carbon black:polyvinylidene fluoride (PVDF) = 8:1:1. N-methylpyrrolidone was added to prepare a cathode slurry with a solid content of 55%. This slurry was uniformly coated onto carbon-coated aluminum foil, vacuum dried, rolled, and punched into a 2.01 cm² area. 2 Electrode assembly. The negative electrode uses a lithium metal sheet, the separator uses Celgard 2400PE film, and the electrolyte uses a commercially available product (SS-SHRG004, Dongguan Shanshan Battery Materials Co., Ltd.). The positive electrode, separator, and negative electrode are assembled in one go in a glove box (high-purity Ar atmosphere), and then the electrolyte (1 mol / L NaClO4 + EC:DMC:EMC(1:1:1) + 5% FEC) is injected to obtain a coin cell.

[0151] The coin cell was subjected to constant current charge-discharge cycle test at 25℃ and 0.1C, with a charge-discharge voltage of 2.0-3.7V. The initial coulombic efficiency was calculated. There was no special test method. The initial coulombic efficiency = initial discharge specific capacity / initial charge specific capacity. The coin cell battery was tested for rate capability at 25℃ and 2C. The test results are shown in Table 1.

[0152] Table 1

[0153] As can be seen from the test results in Table 1, compared with the lithium iron phosphate cathode material prepared using amine ether compounds as a carbon source in Examples 1-6, the lithium iron phosphate cathode material prepared using amine ether compounds as a carbon source in Examples 1-6, under the same residual carbon content, has significantly lower powder resistivity, higher compaction density, and significantly improved initial discharge capacity, initial coulombic efficiency, and 2C rate performance of the prepared coin cells. This indicates that the lithium iron phosphate cathode material prepared using amine ether compounds as a carbon source in Examples 1-6 has excellent electrochemical performance.

[0154] Comparing Example 1, Comparative Example 4, Comparative Example 5, and Comparative Example 6, it is shown that there is a suitable range for the amount of carbon source added. Too much or too little carbon source will lead to a decrease in the amount of residual carbon, resulting in a significant decrease in the electrochemical performance of the obtained battery.

[0155] Comparing Comparative Examples 1-2 and Examples 1-6, it is evident that, with the same total amount of carbon source, the lithium iron phosphate cathode material prepared using amine ether compounds as a carbon source has a significant advantage over the lithium iron phosphate cathode material prepared using PEG compounds as a carbon source. This demonstrates that the molecular structure of the carbon source has a substantial impact on the electrical performance of the battery assembled from the prepared lithium iron phosphate cathode material. The nitrogen atoms in the amine ether compounds in Examples 1-6 facilitate uniform coating of the carbon source and can form cyclic structures during the pyrolysis process, thereby increasing the degree of orderliness of the coated carbon. The lithium iron phosphate cathode material prepared using these compounds exhibits a significant advantage over Comparative Examples 1-2.

[0156] Compared with Example 1, Comparative Example 3 did not contain any amine ether compounds, and lacked the nitrogen atoms that play a special role in amine ether compounds; thus affecting the first discharge capacity and first coulombic efficiency of the resulting coin cell.

[0157] Comparing Examples 1 and 6, it is evident that glucose and amine ether compounds exhibit a stronger synergistic effect as a combined carbon source compared to the combination of PEG and amine ether compounds. The amine ether compounds form a uniform carbon layer through charge adsorption, while glucose fills and forms a dense carbon layer. The absence of either leads to a significant increase in resistivity, affecting the initial discharge capacity and initial coulombic efficiency of the resulting coin cell. Furthermore, after the amine ether compounds adsorb and form a uniform carbon layer, the large steric hindrance of PEG prevents it from effectively filling the spaces between the amine ether compounds, resulting in a certain degree of decrease in the compaction density of the resulting lithium iron phosphate cathode material and a certain degree of decrease in the electrical performance of the resulting coin cell.

[0158] 2. Batteries prepared using lithium manganese iron phosphate as the positive electrode active material

[0159] 85g of lithium manganese iron phosphate cathode material, 5g of polyvinylidene fluoride, 10g of conductive carbon black, and 150mL of N-methylpyrrolidone prepared in the above examples and comparative examples were placed in a beaker and mechanically stirred at 500r / min for 4h to form a slurry. The slurry was coated onto aluminum foil with a single-sided thickness of 80μm using a doctor blade coater. The foil was pre-dried in a 60℃ forced-air drying oven for 30min and then transferred to a 120℃ vacuum drying oven for 12h. The dried electrode was compacted using a roller press with a pressure controlled at 110MPa and cut into electrode sheets with a diameter of 14mm to obtain the cathode. Using lithium foil as the negative electrode and a Celgard 2400 polypropylene microporous membrane as the separator, and 1 mol / L LiPF6 (EC:DEC = 1:1, v / v) as the electrolyte, the positive electrode, negative electrode, separator, and electrolyte were assembled in an argon glove box with water and oxygen content all below 1 ppm. After assembly, the cells were allowed to stand for 24 hours to obtain coin cells. The discharge specific capacity at 0.1C and 5C rates was tested under charge / discharge cutoff voltages of 3.0-4.3V; the capacity retention rate after 100 cycles at 5C charge / discharge rate was also tested. The results are shown in Table 2.

[0160] Table 2

[0161] As can be seen from the test results in Table 2, compared with the lithium iron phosphate cathode material prepared using amine ether compounds as a carbon source in Examples 7-12, the powder conductivity of the lithium iron phosphate cathode material prepared using amine ether compounds as a carbon source is significantly improved under the same residual carbon content. The initial discharge capacity and 5C capacity retention rate of the coin cells prepared are also significantly improved. This indicates that the lithium iron phosphate cathode material prepared using amine ether compounds as a carbon source in Examples 7-12 has excellent electrochemical performance.

[0162] Comparing Example 7, Comparative Example 10, Comparative Example 11, and Comparative Example 12, it is shown that there is a suitable range for the amount of carbon source added. Both excessive and insufficient addition of carbon source will lead to a significant decrease in the electrochemical performance of the resulting battery.

[0163] Comparing Comparative Examples 7-8 and Examples 7-12, it is evident that, with the same total amount of carbon source, the lithium manganese iron phosphate cathode material prepared using amine ether compounds as a carbon source has a significant advantage over the lithium manganese iron phosphate cathode material prepared using PEG compounds as a carbon source. This demonstrates that the molecular structure of the carbon source has a substantial impact on the electrical performance of the battery assembled from the prepared lithium manganese iron phosphate cathode material. The nitrogen atoms in the amine ether compounds of Examples 7-12 facilitate uniform coating of the carbon source and can form cyclic structures during the pyrolysis process, thereby increasing the degree of orderliness of the coated carbon. The lithium manganese iron phosphate cathode material prepared using these compounds exhibits a significant advantage over Comparative Examples 7-8.

[0164] Compared with Example 7, Comparative Example 9 did not contain any amine ether compounds and lacked the nitrogen atoms that play a special role in amine ether compounds; thus affecting the initial discharge capacity and initial coulombic efficiency of the resulting coin cell.

[0165] Comparing Examples 7 and 12, it is shown that glucose and amine ether compounds exhibit a stronger synergistic effect as a combined carbon source compared to the combination of PEG and amine ether compounds. The amine ether compounds form a uniform carbon layer through charge adsorption, while glucose fills and forms a dense carbon layer. The absence of either leads to a significant increase in resistivity, affecting the initial discharge capacity and initial coulombic efficiency of the resulting coin cell. Furthermore, after the amine ether compounds adsorb and form a uniform carbon layer, the large steric hindrance of PEG prevents it from effectively filling the spaces between the amine ether compounds, resulting in a certain decrease in the compaction density of the resulting lithium manganese iron phosphate cathode material and a certain degree of decrease in the electrical performance of the resulting coin cell.

[0166] 3. Batteries prepared using sodium iron manganese phosphate (sodium iron manganese phosphate) as the positive electrode active material for sodium-ion batteries.

[0167] The sodium-ion batteries prepared in the above examples and comparative examples were uniformly mixed with sodium iron manganese phosphate positive electrode material, acetylene black, and PVDF binder, and then coated onto aluminum foil. After vacuum baking at 100°C for 4 hours, electrode sheets were obtained. Based on the total weight of the positive electrode material, acetylene black, and PVDF binder, the amount of positive electrode material was 80 wt%, the amount of acetylene black was 10 wt%, and the amount of PVDF binder was 10 wt%. Using the sodium sheet as the negative electrode, a glass fiber optic GF / A Whatman potassium sodium lithium battery filter membrane was used as the separator, and a 0.8 M NaPF6 / EC-DMC electrolyte was used. Button batteries were assembled and their charge-discharge characteristics were tested. The charge-discharge current was 0.1C, where 1C = 129 mA / g. The discharge specific capacity and average discharge voltage of the comparative and examples are shown in Table 3.

[0168] Table 3

[0169] As can be seen from the test results in Table 3, compared with the sodium iron manganese phosphate cathode material prepared using conventional carbon source PEG, the coin cells prepared using sodium iron manganese phosphate cathode material prepared using amine ether compounds as carbon source in Examples 13-18 showed significant improvements in weight, average discharge voltage, and capacity retention. This indicates that the sodium iron manganese phosphate cathode material prepared using amine ether compounds as carbon source in Examples 13-18 has excellent electrochemical performance.

[0170] Comparing Comparative Examples 13-14 and Examples 13-18, it is evident that, with the same total amount of carbon source, the sodium iron manganese phosphate cathode material prepared using amine ether compounds as a carbon source has a significant advantage over the sodium iron manganese phosphate cathode material prepared using PEG compounds as a carbon source. This demonstrates that the molecular structure of the carbon source has a substantial impact on the electrical performance of the battery assembled from the prepared sodium iron manganese phosphate cathode material. The nitrogen atoms in the amine ether compounds of Examples 13-18 facilitate uniform coating of the carbon source and can form cyclic structures during the pyrolysis process, thereby increasing the degree of orderliness of the coated carbon. The sodium iron manganese phosphate cathode material prepared using these compounds exhibits a significant advantage over Comparative Examples 13-14.

[0171] Compared with Example 13, Comparative Example 15 did not contain any amine ether compounds, and lacked the nitrogen atoms that play a special role in amine ether compounds; thus affecting the first discharge capacity and capacity retention of the resulting coin cell.

[0172] Comparing Example 13 and Comparative Example 16 shows that there is a suitable range for the amount of carbon source added. Too little carbon source will lead to a significant decrease in the electrochemical performance of the resulting battery.

[0173] Comparing Examples 15 and 13, it is shown that glucose and amine ether compounds exhibit a stronger synergistic effect as a combined carbon source compared to the combination of PEG and amine ether compounds. The amine ether compounds form a uniform carbon layer through charge adsorption, while glucose fills and forms a dense carbon layer. The absence of either leads to a significant increase in resistivity, affecting the initial discharge capacity and initial coulombic efficiency of the resulting coin cell. Furthermore, after the amine ether compounds adsorb and form a uniform carbon layer, the large steric hindrance of PEG prevents it from effectively filling the spaces between the amine ether compounds, resulting in a certain decrease in the compaction density of the obtained sodium iron manganese phosphate cathode material and a certain decrease in the electrical performance of the resulting coin cell.

[0174] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and the scope of protection of the present invention is defined by the appended claims. Those skilled in the art can make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but all such changes and modifications fall within the scope of protection of the present invention.

Claims

1. A raw material composition for a positive electrode material, characterized in that, It includes a carbon source; the carbon source includes amine ether compounds; the amine ether compounds account for 40%-62% of the mass percentage of the carbon source.

2. The raw material composition for the positive electrode material as described in claim 1, characterized in that, The raw material composition of the positive electrode material satisfies (1) and / or (2) of the following conditions: (1) The amine ether compound has the structure shown in Formula I: Equation I; Among them, R1 and R2 are each independently selected from -H, straight chain or branched C. 1-10 Alkyl groups, such as -H; Among them, R3 is selected from the C of straight chain or branched chain. 1-20 Alkyl, -M7R9, or phenyl; The C of the straight chain or branched chain 1-20 Alkyl groups are preferably straight-chain C4 groups. 12 alkyl; In the -M7R9, M7 is selected from... n is selected from 1 to 5000, preferably 5 to 10, for example 6; R 11 Selected from -H, -CH3, or -CH2CH3, for example -H; R9 is selected from -H, straight-chain, or branched C. 1-10 Alkyl groups, such as -H; M1 or M2 are each independently selected from n is selected from 1 to 5000, preferably 3 to 10, for example 5; R 11 Selected from -H, -CH3, or -CH2CH3, for example -H; (2) The amine ether compound has the structure shown in Formula II: Formula II; Among them, R4 is selected from the C of straight chain or branched chain. 2-12 Alkylene or -CH2CH2N(M8R) 10 CH2CH2-; The C of the straight chain or branched chain 2-12 The alkylene group is preferably a straight-chain C2 alkylene group; The -CH2CH2N(M8R) 10 In CH2CH2-, M8 is selected from n is selected from 1 to 5000, preferably 3 to 15, for example 7; R 11 Selected from -H, -CH3, or -CH2CH3R5, for example -H; R 10 C selected from -H, straight chain or branched chain 1-10 Alkyl groups, such as -H; Among them, R5, R6, R7, and R8 are each independently selected from -H, straight chain, or branched C. 1-10 Alkyl groups, such as -H; Among them, M3, M4, M5, or M6 are each independently selected. n is selected from 1-5000, preferably 3-15, for example 6 or 7; R 11 Selected from -H, -CH3, or -CH2CH3, for example -H.

3. The raw material composition for the positive electrode material as described in claim 1, characterized in that, The raw material composition of the cathode material satisfies any one of the following conditions: The amine ether compound has the structure shown in Formula I as described in claim 2, wherein R3 is selected from C. 12 Alkyl; M1 is selected from n is 5, R 11 Selected from -H; R1 is selected from -H; M2 is selected from R 11 Selected from -H, n is 5; R2 is selected from -H; or, The amine ether compound has the structure shown in Formula I as described in claim 2, wherein R1 is selected from -H; M1 is selected from... R 11 Selected from -H, n is 6; M2 is selected from R 11 Selected from -H, n is 6; R2 is selected from -H; R3 is selected from -M7R9, M7 is selected from R 11 Selected from -H, n is 6, R9 is selected from -H; or, The amine ether compound has the structure shown in Formula I as described in claim 2, wherein R1 is selected from -H; M1 is selected from... R 11 Selected from -H, n is 5; M2 is selected from R 11 Selected from -H, n is 5; R2 is selected from -H; R3 is selected from phenyl; or, The amine ether compound has the structure shown in Formula II as described in claim 2, wherein R4 is selected from a straight-chain C2 alkylene group; M3 is selected from... R 11 Selected from -H, n is 6; R5 is selected from -H; M4 is selected from R 11 Selected from -H, n is 6; R6 is selected from -H; M5 is selected from R 11 Selected from -H, n is 6; R7 is selected from -H; M6 is selected from R 11 Selected from -H, n is 6; R8 is selected from -H; or, The amine ether compound has the structure shown in Formula II as described in claim 2, wherein R4 is selected from -CH2CH2N(M8R) 10 CH2CH2-; M8 is selected from R 11 Selected from -H, n is 7; R 10 Selected from -H; M3 selected from R 11 Selected from -H, n is 7; R5 is selected from -H; M4 is selected from R 11 Selected from -H, n is 7; R6 is selected from -H; M5 is selected from R 11 Selected from -H, n is 7; R7 is selected from -H; M6 is selected from R 11 Selected from -H, n is 7; R8 is selected from -H.

4. The raw material composition for the positive electrode material as described in claim 1, characterized in that, The raw material composition of the positive electrode material satisfies (1) and / or (2) of the following conditions: (1) The amine ether compound accounts for 45%-62% of the mass of the carbon source, for example, 50%, 53.8%, 45.5%, 55.6% or 60%; (2) The carbon source accounts for 3%-20% of the mass of the raw material composition of the cathode material, preferably 5%-65%, such as 8.9%, 9.5%, 8.2%, 5.3%, 5.8% or 12%.

5. The raw material composition for the positive electrode material as described in claim 1, characterized in that, The raw material composition of the positive electrode material satisfies (1) and / or (2) of the following conditions: (1) The carbon source also includes one or more of sucrose, glucose, polyethylene glycol, starch, citric acid and asphalt, such as polyethylene glycol and / or glucose; the polyethylene glycol is preferably PEG1500, PEG6000 or PEG-200; The carbon source comprises glucose and the amine ether compound, wherein the mass ratio of glucose to the amine ether compound is preferably (0.3-3):1, more preferably (0.5-2):1, for example 1:1, 0.85:1, 1.2:1, 0.8:1 or 0.67:11; more preferably, the carbon source comprises dodecylamine polyoxyethylene (10) ether and glucose; the carbon source comprises triethanolamine polyoxyethylene (15) ether and glucose; the carbon source comprises aniline polyoxyethylene (10) ether and glucose; the carbon source comprises ethylenediamine polyoxyethylene (24) ether and glucose; the carbon source comprises diethylenetriamine polyoxyethylene (35) ether and glucose; The carbon source comprises polyethylene glycol and the amine ether compound, wherein the mass ratio of polyethylene glycol to the amine ether compound is preferably (0.5-2):1, more preferably (0.8-1.5):1, for example 1:1, 0.8:1 or 1.25:1; more preferably, the carbon source comprises dodecylamine polyoxyethylene (10) ether and PEG200; (2) The positive electrode material is lithium iron phosphate, lithium manganese iron phosphate or sodium iron manganese phosphate.

6. A method for preparing a positive electrode material, characterized in that, It includes the following steps: sintering the precursor slurry to obtain the cathode material; the precursor slurry includes the raw material composition of the cathode material as described in any one of claims 1-5.

7. The method for preparing the cathode material as described in claim 6, characterized in that, The method for preparing the cathode material satisfies one or more of the following conditions: (1) The sintering temperature is 300-850℃, preferably 400-750℃, for example 480, 550, 700 or 720℃; (2) The sintering time is 1-20h, preferably 2-13h, for example 2, 7, 8, 10 or 12h; (3) The heating rate from room temperature to the sintering temperature is 1-10℃ / min, preferably 2-6℃ / min, for example 3 or 5℃ / min; (4) The sintering is divided into a first-stage sintering and a second-stage sintering, and the temperature of the second-stage sintering is higher than that of the first-stage sintering; The sintering temperature of the first stage is preferably 300-600℃, more preferably 400-500℃, for example 480℃; the sintering time of the first stage is preferably 1-4h, more preferably 2-3h, for example 2h; the heating rate from room temperature to the sintering temperature of the first stage is preferably 3-8℃ / min, more preferably 4-6℃ / min, for example 5℃ / min; The preferred temperature for the second-stage sintering is 500-850℃, more preferably 650-750℃, for example 700℃; the preferred sintering time for the second stage is 5-10h, more preferably 7-9h, for example 8h; and the preferred heating rate from the temperature of the first-stage sintering to the temperature of the second-stage sintering is 1-5℃ / min, more preferably 2-4℃ / min, for example 3℃ / min.

8. A positive electrode material, characterized in that, It is prepared using the method for preparing the positive electrode material as described in claim 6 or 7.

9. An electrode sheet, characterized in that, It includes the cathode material as described in claim 8.

10. A battery, characterized in that, It includes the electrode as described in claim 9.